(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
The aim of this research was to discuss the relationship between the natural conditions level and human actions conducive to environmental protection. The research was made for rural and urban-rural communes of Słupsk and Sławno districts. The analysis was carried out for 2015 based on data published by the Central Statistical Office of Poland. The research was conducted using the synthetic indicator. Based on the selected indicators the diversification level of natural conditions and human actions conducive to environmental protection has been determined. Analysis showed that the best situation occurs in Ustka commune, while the worst occurs both in Malechowo and Główczyce communes.